In-situ holotomography to study longitudinal debonding in glass fibre-reinforced composites - Yentl Swolfs; Thanasis Chatziathanasiou; Martin Diehl; Mahoor Mehdikhani; Christian Breite (e-Journal of Nondestructive Testing)
The formation of fibre breaks governs the longitudinal tensile failure of a unidirectional ply. It is widely believed that matrix plasticity, matrix cracking, and fibre-matrix debonding created near these fibre breaks help reduce the resulting stress concentrations. Therefore, to determine if matrix cracking and fibre-matrix debonding surrounding fibre breaks occur in a glass fibre-epoxy composite, we performed in-situ tensile tests combined with holotomography at a resolution of 150 nm. Despite their presence in single-fibre composites manufactured with the same constituents, they were absent in regular composites. This suggests that single-fibre composites are not representative of regular composites. The study provides fresh insight into the damage mechanisms in these materials.